P370 Multi-disciplinary teams in complex care – insights from the romanian mocha survey data. (6th June 2017) - Roth, Maria; Stativa, Ecaterina; Marginean, Catalina
Abstract : Background: The quality of life of children with complex care needs depends on collaboration between parents and professionals involved in primary and secondary health care services, as well as in social and educational services. Scope: The presentation will discuss the results of expert responses given by Romanian professionals in cases of complex care as part of the EU H2020 MOCHA project. The focus was on children with Epilepsy, Traumatic Brain Injury (TBI), Autism, ADHD, Asthma, and Long Term Mechanic Ventilation (LTV). Methods: Subject experts were asked about regulations, procedures and practices on collaboration in the multidisciplinary teams and asked to provide evidence for their statements. Results: The analysis revealed many gaps in communication between primary and secondary care in both directions, between management of health care, social care and education, and also between professionals and parents, as well as children. When a child has an enduring and complex health condition the collaboration between health care providers and other caretakers is more problematic, and in the absence of e-platforms parents are often responsible for the circulation of information among professionals. In case of children with disabilities collaboration between health, education and social sectors have been recently regulated in Romania by the Governmental Order 1985/1305/5805/2016, accompanied by extensive guidelines on inter-sectoral cooperation, expected to bring significant improvements for multi-disciplinary involvement. For Asthma, Epilepsy and L. T. V, case management procedures are still lacking in Romania. Efforts to develop specific guidance and legislation have been sustained by parents' associations that expect better information, transparency and collaborative work from professionals. Conclusions: The results show recent improvements towards regulating multi-disciplinary cooperation, but there is no evidence of systematic evaluation assessing such collaboration. An e-platform for exchange of child health data is still lacking. Key-words: Multi-disciplinary teams, collaboration, children with complex care needs, case management